(3efVhQ GbJUGOjs - (3Rjf GdYGHOjf Hf YHO Gddg(B, (3HQjs ((3GdQjGV(B:s (3GdfTQ GdYdej hGdeWGHY(B,s, 2005)
(3GdCSGS GdfXQj dNUNUI GdeTQhYGJ GdYGeI(B-(3NUNUI bWGYj Gdfbd hGdEJUGdGJ;NUNUI GdefGaY GdYGeI(B:(3GdeGA hGdcgQHGA(B-(3NUNUI GdNOeGJ GdYGeI(B:(3GdJYdje hGdUMIs
Keywords: (3GdCSYGQs; (3GdEfJGLs; (3GdShbs; (3GdUMIs; (3GdeTQhYGJ GdYGeIs; (3NUNUI GdcgQHGAs